2022
DOI: 10.1111/1365-2745.14045
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects in radial tree growth are rarely significant after accounting for biological memory

Abstract: 1. Drought legacies in radial tree growth are an important feature of variability in biomass accumulation and are widely used to characterize forest resilience to climate change. Defined as a deviation from normal growth, the statistical significance of legacy effects depends on the definition of "normal"-expected growth under average conditions-which has not received sufficient scrutiny.2. We re-examined legacy effect analyses using the International Tree-Ring Data Bank (ITRDB) and then produced synthetic tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 116 publications
(141 reference statements)
2
17
0
Order By: Relevance
“…The Klesse et al (2022) study provides a detailed analysis, using both observed and simulated data, that highlights properties of tree‐ring time series that can impact conclusions about drought legacies. Inspired by this study, we see four major outcomes deserving wider attention in the community: (1) autocorrelation in tree‐ring time series; (2) treatment of pre‐ and postdrought conditions; (3) individual tree idiosyncrasy; and (4) differentiating climate memory and legacies.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…The Klesse et al (2022) study provides a detailed analysis, using both observed and simulated data, that highlights properties of tree‐ring time series that can impact conclusions about drought legacies. Inspired by this study, we see four major outcomes deserving wider attention in the community: (1) autocorrelation in tree‐ring time series; (2) treatment of pre‐ and postdrought conditions; (3) individual tree idiosyncrasy; and (4) differentiating climate memory and legacies.…”
Section: Figurementioning
confidence: 99%
“…Second, treatment of pre-and postdrought climate is essential, where our definition of 'normal' has implications for how 'abnormal' postdrought growth appears. While not discussed in Klesse et al (2022), we argue that analyses should account for the role of postdrought climate in recovery. This is because wetter years may lead to faster recovery, while drier years (perhaps more common in the western United States) may lead to prolonged impairment.…”
mentioning
confidence: 91%
See 3 more Smart Citations